Development And Validation Of First Order Derivative Spectrophotometric Method For Simultaneous Estimation Of Omeprazole And Cinitapride In Pharmaceutical Dosage Form - Y.G. MAKANI,; H.A.RAJ, (International Journal of Pharma and Bio Sciences, 2012)
The use of first order derivative spectrophotometry allowed simultaneous estimation of Omeprazole and Cinitapride, at their respective zero crossing point (ZCP) in fixed dose combination products. The absorbance values at 263.2 nm (ZCP of cinitapride) and 253.8 nm (ZCP of omeprazole) of first derivative spectrum were used for the estimation of Omeprazole and Cinitapride respectively without mutual interference in methanol. The method was found to be linear (r2>0.9995) in the range of 7-42 μg/ml for Omeprazole. The linear correlation was obtained (r2>0.9992) in the concentration range of 1-6 μg/ml for Cinitapride. The method was validated for as per ICH Q2 (R1) guidelines. The limit of determination was 0.06μg/ml and 0.33μg/ml for Omeprazole and Cinitapride, respectively. The limit of quantification was 0.18μg/ml and 1.00μg/ml for Omeprazole and Cinitapride, respectively. The proposed method is simple, rapid, precise and accurate and hence can be successfully applied for the simultaneous determination of Omeprazole and Cinitapride in formulations.